Teaching Communicative Translation through Skopos Theory - Yanny Indrawati (Widya Mandala Surabaya Catholic University, 2010)
Communication is considered successful when the people involved understand each others. Since there are many languages around their world, languages can also be a barrier in communicating. People with a particular language cannot interact with other who has different language than his to link this shortage, it requires the role of a translator. Nowadays many people are just taking the opportunity to be translators just because they are bilingual without any awareness of what it is called as successful in translation People with a particular language cannot interact with other who has different language than his. In this regard, this paper will discuss what aspect are necessary to be a professional translator. This understanding will lead us to know how to teach translation to students in order to achieve a communicative translation.